Envisaged Learning Environments for Learners with Visual Impairments in Lesotho Rural Schools Using Asset-Based Approaches - Ramatea, Mamochana Anacletta; Khanare, Fumane Portia (CV. Literasi Indonesia, 2024)
Previous literature has highlighted the persistent global challenge of providing quality education in conducive settings for learners with visual impairments (LVIs), particularly in rural schools. This study aims to explore viable resources that can be leveraged to create an enabling learning environment for LVIs within rural primary school contexts. Employing a qualitative research approach, the study engaged 12 teachers from rural mainstream primary schools in Lesotho. Data were gathered through focus group discussions with a purposively selected sample of teachers and analyzed thematically. The findings underscored the perception among participants that rural schools possess a range of assets, both visible and concealed, that effectively cater to the special educational needs of LVIs. However, a notable limitation surfaced regarding the teachers' knowledge about utilizing these existing resources optimally. Consequently, this highlighted a crucial need for enhanced collaboration, involvement of relevant stakeholders, and augmentation of academic resources. The effective utilization of these assets emerges as a pivotal factor requiring improved management to cultivate a more conducive learning environment for LVIs in the future.